Qualitative analysis of some bioactive components of methanolic leaf extract of M. citrifolia (Noni) - Haruna, Aishatu; Ismail, Siti Izera; Omar, Dzolkhifli; Mohamed, Mahmud Tengku Muda (Journal of Medicinal Herbs and Ethnomedicine, 2020)
Medicinal plants offer endless opportunities for new drugs discovery due to their supremacy for the possession of phytochemicals compounds known for diverse antimicrobial activities. The world ever increasing demand for therapeutic drugs from natural products with particular interest in edible plants for safety purposes is now catching researchers’ attention. This study therefore aimed at determining the presence of some bioactive phytochemical components of methanolic leaf extract of M. citrifolia L. Qualitative screening of leaf extract has confirmed the existence of Tannins, steroids, saponins, flavonoids and alkaloids in the mixture. And these bioactive compounds correspond to phytochemicals with antimicrobial, nematicide, pesticidal, antioxidant, ant-inflammatory, cytotoxic, anti-allergy, and anti-carcinogenic properties (bioactive compounds) earlier documented by previous researchers.